The Essence of The Tradition of Worrying Graves According to The Community of Tanjung Medan Village, Kampung Rakyat, South Labuhabatu - Harahap, Sapta Emier Hamdi; Adenan, Adenan; Harahap, Aprilinda (International Journal of Nusantara Islam, 2024)
This study aims to understand the religious traditions in Tanjung Medan Village, which are an integral part of the social and cultural life of the local community. This study used descriptive qualitative methods with a religious anthropological approach. This approach was chosen to view religion as a social phenomenon that reflects identity, values, and symbols in the community. The research used a descriptive qualitative method. The approach used is religious anthropology, which aims to understand religious traditions in Tanjung Medan Village as a part of the social and cultural life of the local community. This approach helps researchers see religion not only as a spiritual aspect, but also as a social phenomenon that reflects the identities, values, and symbols that live in the community. The results of this research show that the tradition of reciting the Qur’an in graves in Tanjung Medan Village is a form of cultural acculturation between Islamic teachings and pre-existing local traditions. The people of Tanjung Medan Village solemnly carry out this tradition as a tribute to the deceased and as a reminder to those who are still alive about life after death. In its implementation, this tradition not only involves the immediate family but also the surrounding community, such as the Wirid group, who participate in reading prayers and verses from the Qur’an. In addition, this activity contains values of togetherness and solidarity, which are demonstrated in the reading of the Qur’an alternately by several people and in the provision of alms for participants. Overall, the tradition of reciting the Qur’an at graves In Tanjung Medan Village not only functions as a tribute to the dead but also as a means of conveying Islamic values in a way that is simple and easily accepted by the community